2006
DOI: 10.1063/1.2393162
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale fabrication of single-phase Er2SiO5 nanocrystal aggregates using Si nanowires

Abstract: Single-phase Er 2 SiO 5 nanocrystal aggregates were produced on a large scale using Si nanowire ͑Si-NW͒ arrays as templates. A dense array of Si-NWs was grown by vapor-liquid-solid mechanism using Au catalyst on Si ͑111͒ substrate. Afterwards, ErCl 3 ·6H 2 O dissolved ethanol solution was spin coated and annealed first at 900°C for 4 min in a flowing N 2 /O 2 environment and then at 1200°C in a flowing Ar environment for 3 min. X-ray diffraction, scanning electron microscope, and high-resolution transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
(21 reference statements)
1
33
0
Order By: Relevance
“…In this work we describe the growth, processing, and optical properties of single-crystal Er 2 O 3 -on-Si (EOS). Similar to stoichiometric polycrystalline Er 3+ materials [15][16][17][18][19][20], EOS allows for a 100-fold increase in Er 3+ concentration over conventional Er-doped glasses [21], making it an attractive material for on-chip emission and amplification in the 1550-nm wavelength band. Developed simultaneously for optoelectronic [22] and high-κ dielectric [23] applications, epitaxially grown Er 2 O 3 films can be incorporated into precisely controlled heterostructures and superlattices, which may also allow for efficient electrical injection.…”
mentioning
confidence: 99%
“…In this work we describe the growth, processing, and optical properties of single-crystal Er 2 O 3 -on-Si (EOS). Similar to stoichiometric polycrystalline Er 3+ materials [15][16][17][18][19][20], EOS allows for a 100-fold increase in Er 3+ concentration over conventional Er-doped glasses [21], making it an attractive material for on-chip emission and amplification in the 1550-nm wavelength band. Developed simultaneously for optoelectronic [22] and high-κ dielectric [23] applications, epitaxially grown Er 2 O 3 films can be incorporated into precisely controlled heterostructures and superlattices, which may also allow for efficient electrical injection.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the erbium compounds, the density of erbium ions is 10 22 atoms/cm 3 , which is orders of magnitude greater than that typically obtained by Er ion implantation in silicon substrate, allowing access to a large number of emitting centers.…”
mentioning
confidence: 99%
“…Previous work revealed that the processes in the growth methods significantly affect the photoluminescence (PL) intensities of Er +3 ions in the materials. [1][2][3][4][5][6][7][8] According to Ref. 7, for example, the PL intensity of Er 2 O 3 grown on Si and SiO 2 by magnetron sputtering becomes large with an increase of annealing temperature up to 1200…”
mentioning
confidence: 99%
“…Some of these methods include utilization of sensitizers such as silicon nanoclusters, [7][8][9][10][11] incorporation of Er in Si x N y , 12 co-implantation of silver in silica glass, 13 preparation of multilayers of Er-doped SiO 2 with silicon rich silicon dioxide ͑SRSO͒, [14][15][16] and synthesis of Er-doped oxide nanostructures. 17,18 Much research effort has also been directed in determining the absorption cross sections for these material systems. For example, the photoluminescence ͑PL͒ rise time measurements have been used to determine an enhanced effective excitation absorption cross section of 1.1 ϫ 10 −16 cm of Er in SiO 2 and the slight improvement in peak absorption cross section with Si inclusion, SiO 2 turns out to be an unsuitable host material for miniaturizing compact planar optical waveguides, leaving groups to turn to alternative host materials.…”
Section: Introductionmentioning
confidence: 99%